2018
DOI: 10.15252/embj.201798133
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cell–cell contacts and RhoA/ MRTF ‐A signaling regulates cardiomyocyte identity

Abstract: Cell–cell and cell–matrix interactions guide organ development and homeostasis by controlling lineage specification and maintenance, but the underlying molecular principles are largely unknown. Here, we show that in human developing cardiomyocytes cell–cell contacts at the intercalated disk connect to remodeling of the actin cytoskeleton by regulating the RhoA‐ROCK signaling to maintain an active MRTF/SRF transcriptional program essential for cardiomyocyte identity. Genetic perturbation of this mechanosensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 75 publications
5
61
0
Order By: Relevance
“…51 Because cell shape change is facilitated by disruption of the actin cytoskeleton, this disruption is required for all white, brown, and beige adipocyte differentiation 52 ; some recent studies indicated that the inhibition of RhoA and ROCK-mediated actin cytoskeleton dynamics is required for all three types of adipogenesis. 31,39,40 Our observations in this study provide direct support for a negative role of ROCK2 activity in beige adipogenesis in vivo and in vitro, accordingly linking ROCK2 with previously known RhoA/ ROCK upstream and downstream signaling pathways; we therefore further recognize the important metabolic impacts of ROCK2 in obesity. The other result noteworthy is that we found an inverse relationship between ROCK2 activity (and total ROCK activity) and the abundance of brown/beige adipocytes in fat depots (Figure 2; Figure S2), further supports the notion that ROCK2 activity inhibits beige adipogenesis through promoting actin cytoskeleton dynamics.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…51 Because cell shape change is facilitated by disruption of the actin cytoskeleton, this disruption is required for all white, brown, and beige adipocyte differentiation 52 ; some recent studies indicated that the inhibition of RhoA and ROCK-mediated actin cytoskeleton dynamics is required for all three types of adipogenesis. 31,39,40 Our observations in this study provide direct support for a negative role of ROCK2 activity in beige adipogenesis in vivo and in vitro, accordingly linking ROCK2 with previously known RhoA/ ROCK upstream and downstream signaling pathways; we therefore further recognize the important metabolic impacts of ROCK2 in obesity. The other result noteworthy is that we found an inverse relationship between ROCK2 activity (and total ROCK activity) and the abundance of brown/beige adipocytes in fat depots (Figure 2; Figure S2), further supports the notion that ROCK2 activity inhibits beige adipogenesis through promoting actin cytoskeleton dynamics.…”
Section: Discussionsupporting
confidence: 72%
“…[24][25][26][27] In addition, increased actin stress fiber formation facilitates nuclear translocation of MRTF-A, which is a transcriptional cofactor of serum response factor leading to increased actin cytoskeleton gene expression and decreased PPARγ activity. 31,39,40 Our observations in this study provide direct support for a negative role of ROCK2 activity in beige adipogenesis in vivo and in vitro, accordingly linking ROCK2 with previously known RhoA/ F I G U R E 8 Schematic summary of roles of ROCK2 activity in regulating adipogenesis, obesity, and insulin resistance. 51 Because cell shape change is facilitated by disruption of the actin cytoskeleton, this disruption is required for all white, brown, and beige adipocyte differentiation 52 ; some recent studies indicated that the inhibition of RhoA and ROCK-mediated actin cytoskeleton dynamics is required for all three types of adipogenesis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Inactivating Pitx2 in postnatal cardiomyocytes that are regenerating caused accumulation of adipose-like cells within the myocardium, similar to the phenotype that is observed in ARVC patients. The pathological adipose tissue that is found in ARVC patients is thought to be derived from cardiomyocytes of the second heart field and/or bi-potent Isl1 + Wt1 + cell populations (Dorn et al, 2018;Lombardi et al, 2009). In contrast, genetic lineage tracing with the mTmG double-fluorescent Cre reporter of Pitx2 CKO animals injured at P2 showed that the fat cells were of non-myocyte origin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dynamic assembly and disassembly of microfilaments (filamentous (F)-Actin) from G-actin monomers is generally important in cell integrity and control of mobility (31) and specifically important for the establishment of a circumferential F-actin belt parallel to the cell-cell contact area (32). Such microfilament structure is regulated by RhoA GTPase to control membrane rigidity and prevent anchorage detachment (33,34). We found that RhoA activity was decreased upon DSG2 suppression but increased when DSG2 was ectopically expressed (SI Appendix, Fig.…”
Section: Dsg2 Expression Promotes Metastatic Colonization and Tumor Gmentioning
confidence: 99%